Gambaran kualitas hidup pada remaja sekolah menengah atas dengan berat badan berlebih di Kota Kotamobagu pascapandemi COVID-19 - Inggitakirana, Dewa Ayu; Sapulete, Margareth Rosalinda; Porajow, Zwingly Christian Jefferson Gerard (UNIVERSITAS SAM RATULANGI, 2024)
Background: Adolescents who are individuals aged between 10 and 19 years, are facing health problems, one of which is being above normal weight. The fatten adolescents tend to have a lower quality of life (QoL) compared to adolescents with normal nutritional status. Aim: To determine the QoL of the high school adolescents with excess weight in Kotamobagu City post-COVID-19 pandemic. Methods: This study was a quantitative descriptive study with a cross-sectional design, with a cluster random sampling technique. We used the World Health Organization Quality of Life-BREF (WHOQOL-BREF) and measure the height and weight of the participants. Results: The study involved 353 adolescents, 14.4% of whom were excess weight. The study showed that the excess weight participants had QoL in physical health domain of 66.03±9.67 (42.85 - 85.71), psychological domain of 60.29±17.02 (16.67 - 91.67), social relationship domain of 57.02±13.16 (16.67 - 83.33), environmental domain of 64.03±15.06 (31.25 - 90.62). Conclusion: The QoL of high school adolescents with excess weight in Kotamobagu City post-COVID-19 pandemic has increased in all aspects. However, globally, the QoL is adequate in environmental domain and are quite lower in physical health, psychological, and social relationship aspects. Keywords: quality of life, adolescents, excess weight